Reformation und die Ethik der Wirtschaft - Di Fabio, Udo (Mohr Siebeck, 2018)
The grand thesis that the spirit of Protestantism is one of modern capitalism's great driving forces originated from Max Weber. According to him, religious foundations of inner world asceticism, Luther's concept of vocation, Calvinism, and English Puritanism had a direct influence on the development of modern kinds of economy. The thesis was not undisputed and to this day remains a prominent starting point for discussions. What can be said now in the twenty-first century about the spirit of capitalism? Do ethics still hold any sway over global financial markets and systems of production? This volume's four authors seek answers to these and other related questions from different perspectives.